Abgrenzung und Gliederung der Hochgebirgsstufe der Alpen mit Hilfe von Solifluktionsformen - Furrer, Gerhard; Durido, Guido (ERDKUNDE, 1972)
The IGU Commission on High-Altitude Geoecology proposes the following three criteria for the delineation of the high-mountain area: the upper limit of forest, the snow line of the glacial period, and the lower limit of the soli fluidal processes currently at work. In the research presented here the delineation of the so called high region of the Swiss Alps follows the third criterion, i.e., the use of certain forms of solifluction that takes place under the vegetation cover, called Girlanden (see Fig. 3) and Wanderblöcke (shifting boulders). These solifluidal forms are mapped in the field along chosen routes. Their vertical distribution reveals a frequency of occurrence of a normal distribution Hence, within a zone of ± one standard deviation from the average altitude of the phenomenon in question, nearly 70% of all the findings of that particular form should be situated. This is called the core zone. (See Figs. 1-3.) The limit of solifluction is defined as the arithmetic average of lower limits of the core zone of Wanderblöcke and Girlanden. The limit of solifluction was determined for forty-eight areas within the Swiss Alps and thereupon statistically generalized with the use of a regression equation (Fig. 4).